The Potential Role of Gut Microbial-Derived Exosomes in Metabolic-Associated Fatty Liver Disease: Implications for Treatment - Zhang, Binbin; Zhao, Jianan; Jiang, Minjie; Peng, Dandan; Dou, Xiaobing; Song, Yu; Shi, Junping (Frontiers in Immunology, 2022)
The prevalence and incidence of metabolic-associated fatty liver disease (MAFLD), a clinically heterogeneous disease whose primary clinical therapies include dietary control and exercise therapy, is increasing worldwide and constitutes a significant medical burden. Gut microbes influence the physiopathological processes of the liver through different mechanisms based on the gut-liver axis. Exosomes are essential carriers of intercellular communication. Most previous studies have focused on adipocyte- and hepatocyte-derived exosomes, while the critical role of microbial-derived exosomes and the molecular mechanisms behind them in MAFLD have received little attention. Therefore, we searched and screened the latest relevant studies in the PubMeb database to elucidate the link between microbial-derived exosomes and the pathogenesis of MAFLD, mainly in terms of insulin resistance, intestinal barrier, inflammatory response, lipid metabolism, and liver fibrosis. The aim was to provide a theoretical framework and support for clinical protocols and innovative drug development.